FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PARTISIPASI ANGKATAN KERJA AKTIF DI INDONESIA - Nazwa Naisniatunnisa Sholihah; Mirna Nur Alia Abdullah (Yayasan Literasi Sains Indonesia, 2024)
This study explores the factors influencing Indonesian community participation in the labor force, employing a descriptive qualitative method with data collection through literature review. Although Indonesia possesses significant human resource potential that could support economic growth and compete globally, employment issues remain a substantial challenge. Despite the increasing number of people entering the working age, the availability of job opportunities has not kept pace, leading to an imbalance between labor supply and demand. This research identifies three key factors affecting active labor force participation: unemployment, education, and minimum wage. The study is relevant to the Labor Demand Theory, which explains how imbalances in the labor market affect workforce decisions. By understanding these factors, it is hoped that the government can formulate effective policies to create new job opportunities and support economic growth and community well-being more comprehensively. This research aims to provide useful insights for policy-making that could enhance labor force participation and address employment issues in Indonesia.